2020
DOI: 10.1101/2020.12.03.20243394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opportunities to catalyze improved healthcare access in pluralistic systems: a cross-sectional study in Haiti

Abstract: SUMMARYIntroductionGains to ensure global healthcare access are at risk of stalling because some old resilient challenges require new solutions. Our objective was to study a pluralistic healthcare system that is reliant on both conventional and non-conventional providers to discover opportunities to catalyze renewed progress.MethodsA cross-sectional study was conducted among households with children less than 5 years of age in Haiti. Households were randomly sampled geographically with stratifications for popu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…INACT-1 found that families sought care for 32% of pediatric health events. 23 The 2016 DHS in Haiti found that children under 5 sought care for 40.4% of acute respiratory infections and 32.9% of diarrheal cases. 33 These figures were averaged to estimate 35.1% of families with a sick child seek care.…”
Section: Ethicsmentioning
confidence: 99%
See 2 more Smart Citations
“…INACT-1 found that families sought care for 32% of pediatric health events. 23 The 2016 DHS in Haiti found that children under 5 sought care for 40.4% of acute respiratory infections and 32.9% of diarrheal cases. 33 These figures were averaged to estimate 35.1% of families with a sick child seek care.…”
Section: Ethicsmentioning
confidence: 99%
“…During INACT-2, 30% of families paid in full and 25% paid in part (250 gourdes, 2.89). 23 We conservatively assumed the same ratio for these analyses. Daily wages were estimated from the mean per capita gross national income.…”
Section: Ethicsmentioning
confidence: 99%
See 1 more Smart Citation